Fabrication of hydrophobic structures on coronary stent surface based on direct three-beam laser interference lithography - 高龙岳 周玮琦 王渊博 王斯琦 白冲 李仕明 刘斌 王珺楠 崔承坤 李永亮 (Optoelectronics letters, 2016)
To solve the problems with coronary stent implantation, coronary artery stent surface was directly modified by three-beam laser interference lithography through imitating the water-repellent surface of lotus leaf, and uniform mi- cro-nano structures with the controllable period were fabricated. The morphological properties and contact angle （CA） of the microstructure were measured by scanning electron microscope （SEM） and CA system. The water repellency of stent was also evaluated by the contact and then separation between the water drop and the stent. The results show that the close-packed concave structure with the period of about 12 μm can be fabricated on the stent surface with special parameters （incident angle of 3°, laser energy density of 2.2 J.cm2 and exposure time of 80 s） by using the three-beam laser at 1 064 nm, and the structure has good water repellency with CA of 120°.